Long-term results and recurrence patterns from SCALOP: a phase II randomised trial of gemcitabine- or capecitabine-based chemoradiation for locally advanced pancreatic cancer - Hurt, C; Falk, S; Crosby, A; MacDonald, A; Ray, R; Joseph, G; Staffurth, J; Abrams, R; Griffiths, G; Maughan, T; Mukherjee, S (Cancer Research UK, 2017)
Background: SCALOP, a randomised, phase II trial, tested the activity and safety of gemcitabine (GEM)-based and capecitabine (CAP)-based chemoradiation (CRT) for locally advanced pancreatic cancer (LAPC). Here we present the long-term outcomes. Methods: Eligibility: histologically proven LAPC p7 cm. Following 12 weeks of induction GEMCAP chemotherapy (three cycles: GEM 1000 mg m 2 days 1, 8, 15; CAP 830 mg m 2 days 1–21 q28 days) patients with stable/responding disease, tumour p6 cm, and WHO Performance Status 0–1 were randomised to receive one cycle GEMCAP followed by CAP (830 mg m 2 b.d. on weekdays only) or GEM (300 mg m 2 weekly) with radiation (50.4 Gy per 28 fractions). Results: One-hundred fourteen patients (28 UK centres) were registered between 24 December 2009 and 25 October 2011, and 74 were randomised (CAP-RT ¼ 36; GEM-RT ¼ 38). At the time of this analysis, 105 of the 114 patients had died and the surviving 9 patients had been followed up for a median of 10.9 months (IQR: 2.9–18.7). Updated median OS was 17.6 months (95% CI: 14.6– 22.7) in the CAP-CRT arm and 14.6 months (95% CI: 11.1–16.0) in the GEM-CRT arm (intention-to-treat adjusted hazard ratio (HR): 0.68 (95% CI: 0.38–1.21, P ¼ 0.185)); median progression-free survival (PFS) was 12.0 months (95% CI: 10.0–15.2) in the CAP-CRT arm and 10.4 months (95% CI: 8.8–12.7) in the GEM-CRT arm (intention-to-treat adjusted HR: 0.60 (95% CI: 0.32–1.14, P ¼ 0.120)). In baseline multivariable model, age X65 years, better performance status, CA19.9o613 IU l 1 , and shorter tumour diameter predicted improved OS. CAP-CRT, age X65 years, better performance status, CA19.9 o46 IU ml 1 predicted improved OS and PFS in the pre-radiotherapy model. Nine-month PFS was highly predictive of OS. Conclusions: CAP-CRT remains the superior regimen. SCALOP showed that patients with CA19.9 o46 IU ml 1 after induction chemotherapy are more likely to benefit from CRT.